Human-Anatomy Augmented Reality Application (HARA) / Hillary Ata Serit - Serit, Hillary Ata (2015)
Human anatomy is the study of the structure of the human body. Tremendous of memorizing and understanding process that involve in order to learn this topic which very challenging for students in form 4 and 5. Currently, at school the only material for learning human anatomy is through textbook. This situation lead to difficulties for students to learn human anatomy because textbook have limited 3D presentation. Therefore, this project is conducted by aim to use augmented reality (AR) technology to reduce the limitation. Augmented reality allows the superimposing of computergenerated images over real scenes in real time. The application will be develop based on the ADDIE model methodology. There are five phases that involve in this project which are Analysis, Design, Development, Implementation and Evaluation. Each phases contain several activity and deliver. Usability testing will take place at end of this project as an evaluation for knowing how well the application was develop. The result of the evaluation is shown that augmented reality introduced the new technology that suitable for learning human anatomy. Lastly, this project also can give a benefits to future developer that want to develop the augmented reality system.